Exploring the first pressure injury and characteristics of subsequent pressure injury accrual following spinal cord injury. (2nd November 2021) - Harper, Alexandra E.; Terhorst, Lauren; Brienza, David; Leland, Natalie E.
Abstract : Context/Objective: Clinicians have guidance on prevention and treatment of pressure injuries, but little is known regarding characteristics of patients who develop additional pressure injuries. Thus, our objective was to explore the first pressure injury and characteristics of individuals who develop subsequent pressure injuries during acute care and inpatient rehabilitation following spinal cord injury. Design: Secondary analysis of longitudinal data from a cohort of adults following initial traumatic spinal cord injury. Setting: Urban acute care hospital and inpatient rehabilitation facilities. Participants: A convenience sample of adults ( n  = 38) who developed at least one pressure injury during acute care and inpatient rehabilitation. Interventions: Not applicable. Outcome Measures: The primary outcomes were number of additional pressure injuries and stage of care during which they occurred, prior to community discharge. Results: A covariate-adjusted model revealed that participants with ASIA D injury had a 67% decrease in the rate of additional pressure injury incidence compared to participants with ASIA A injury (Rate Ratio = .33, 95% CI [0.13, 0.88]). The severity of the first pressure injury had no significant association with subsequent pressure injury incidence ( P  = .10). Conclusion: These findings indicated that individuals with greater sensory and motor loss had an increased risk of developing additional pressure injuries compared to individuals with less impairment. These results are meaningful for stakeholders interested in understanding factors associated with developing subsequent pressure injuries during the index rehabilitation stay and provide a foundation for future research in this area.